The Parenting of Career Woman to Form Independent Personality: A Case Study of Two Mother In Pinanggripan Village - Wilma Winanda Putri Sirait; Yusnadi; Muhammad Takwin Machmud (International Journal of Educational Practice and Policy, 2023)
The purpose of this study was to find out the parenting style adopted by 2 career women in forming the independence of their children, Mrs. D (33) and Mrs. I (27) in Pinanggripan Village. The type of research is qualitative research using the case study approach. The subject of study was determined through the purposive sampling technique. The data were collected through the interview techniques by using interview form. The results of the study shown that the two informants used typical democratic parenting. Consequently, the children show a good attitude shifting in which children are more independent. In addition, the form of independence can be seen from seven indicators, including: (1) physical ability, (2) self-confidence, (3) responsibility, (4) discipline, (5) good at getting along, (6) sharing, (7) being able to control the emotions. The result shows the child has good independent personality.